1984
DOI: 10.1093/eurheartj/5.suppl_f.129
|View full text |Cite
|
Sign up to set email alerts
|

The hypertrophied myocardium accumulates the MB-creatine kinase isozyme

Abstract: Myocardial hypertrophy was produced in the dog by volume overload, secondary to hypertension, and pressure overload to left or right ventricles and in the rat by pressure overload to the left or right ventricles, by elevating thyroxine-levels and secondary to spontaneous hypertension in order to test whether there are changes in the creatine kinase system in hypertrophied heart. Although there was little or no change in total creatine kinase activity, there were changes in the distribution of the creatine kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
1
2

Year Published

1987
1987
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(33 citation statements)
references
References 0 publications
5
25
1
2
Order By: Relevance
“…In the present study, serum CK-MB, m-GOT and HBD transiently increased 1 day after coronary artery occlusion. The changes in the serum enzyme levels with time after coronary artery occlusion were in agreement with previously reported clinical data in patients with AMI, [15][16][17][18] which would seem to confirm infarction. Indeed, extensive transmural anteroinferior myocardial infarction was observed.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, serum CK-MB, m-GOT and HBD transiently increased 1 day after coronary artery occlusion. The changes in the serum enzyme levels with time after coronary artery occlusion were in agreement with previously reported clinical data in patients with AMI, [15][16][17][18] which would seem to confirm infarction. Indeed, extensive transmural anteroinferior myocardial infarction was observed.…”
Section: Discussionsupporting
confidence: 92%
“…Basically, such an isoenzyme shift is known to occur in the heart under chronic pathological conditions, as, e.g., in hypertrophy, characterized by a compromised cellular energy state (15,20,45,52). First, higher levels of BCK protein led to an increase in the enzymatic activity of BBCK and MBCK, which may efficiently compensate for an inhibition of other CK isoenzymes, mainly MMCK.…”
Section: Discussionmentioning
confidence: 99%
“…In rat models of LVH, the greatest abnormalities of intracellular enzyme composition and bioenergetics were also associated with the more severe later stages of LVH (36).…”
Section: Myocardial Bloodflow Myocardial Blood Flows Measuredmentioning
confidence: 92%
“…These considerations suggest that the causes of the abnormalities in HEP levels in severely hypertrophied myocardium are complex and likely reflect alterations of many cellular characteris- enzyme activity in hypertrophied myocardium. Ingwall et al (36,37) found an increased percentage of the fetal-type isoenzyme ofCK, but decreased mitochondrial CK activity in moderately hypertrophied myocardium. Saturation transfer 31P-NMR studies in the setting of myocardial hypertrophy have suggested that CK forward flux is reduced (as compared with normal) during inotropic stimulation (38).…”
Section: Myocardial Bloodflow Myocardial Blood Flows Measuredmentioning
confidence: 98%